2015
DOI: 10.1186/s12884-015-0608-y
|View full text |Cite
|
Sign up to set email alerts
|

Serum screening in first trimester to predict pre-eclampsia, small for gestational age and preterm delivery: systematic review and meta-analysis

Abstract: BackgroundEarly assessment before the establishment of placental dysfunction has the potential to improve treatment and prognosis for clinical practice.The objective of the study is to investigate the accuracy of serum biochemical markers(Pregnancy- Associated Plasma Protein-A (PAPP-A), human Chorionic Gonadotropin (hCG), Placental Growth Factor (PlGF), Placental Protein 13 (PP13) used in first trimester serum screening in predicting preelampsia, small for gestational age (SGA) and preterm delivery.MethodsThe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
77
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 51 publications
3
77
0
1
Order By: Relevance
“…PlGF was superior to other single markers (PAPP-A, hCG and placental protein 13) but these first trimester markers had low accuracy for prediction of pre-eclampsia. Importantly, the predictive accuracy of first trimester markers was not poorer than that of second trimester markers [55]. In our study we observed that PAPP-A was higher in nulliparous than in multiparous women, which is an unexplained finding also observed in an earlier study [56].…”
Section: Discussionsupporting
confidence: 81%
“…PlGF was superior to other single markers (PAPP-A, hCG and placental protein 13) but these first trimester markers had low accuracy for prediction of pre-eclampsia. Importantly, the predictive accuracy of first trimester markers was not poorer than that of second trimester markers [55]. In our study we observed that PAPP-A was higher in nulliparous than in multiparous women, which is an unexplained finding also observed in an earlier study [56].…”
Section: Discussionsupporting
confidence: 81%
“…Zhong et al [20] summarized these results in a recently published meta-analysis and concluded that PlGF is a good predictive marker for PE, especially PE occurring before 34 weeks of gestation. Less information exists on the behavior of PlGF before 11 weeks of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…[1316] A recent systematic review of first trimester biomarkers to predict SGA reported that biomarkers alone had low predictive accuracy but speculated that performance would improve with addition of clinical characteristics and uterine artery Doppler. [17] An increase in predictive performance for SGA has been reported, after addition of first trimester biomarkers and uterine artery Doppler to clinical risk factors. [18]…”
Section: Introductionmentioning
confidence: 99%